PELAKSANAAN KEPEMIMPINAN OLEH LURAH DALAM UPAYA MENINGKATKAN EFEKTIVITAS KERJA PEGAWAI PADA KANTOR KELURAHAN TONJONG KECAMATAN MAJALENGKA - Yudhanegara, Firman (Jurnal Ilmu Administrasi CENDEKIA, 2019)
ABSTRACTThis study was conducted to determine the extent of the relationship between the leadership of the Lurah and the effectiveness of the work of employees at the Tonjong Village Office, Majalengka District, which is one indicator that can be used as a benchmark for the success of implementing the tasks and functions of the Village Head. Based on the author's observations during the study at the Tonjong Kelurahan Office in Majalengka District, several problem indicators were still found which showed that the effectiveness of the work of employees at the Tonjong Kelurahan office in Majalengka District was still not optimal. After processing the respondent's answer data it turns out that: (1) The implementation of the leadership of the Village Head of Tonjong, especially in the application of leadership techniques has only reached 57.38% and the effectiveness of the work of employees at the Office of the Village Head of Tonjong has only reached 56%. (2) There is a relationship between the application of leadership techniques and employee work effectiveness. The application of leadership that has not been optimal also affects the work effectiveness of employees who are also not optimal. (3) In applying leadership techniques by the Village Chief, Tonjong there are obstacles and there are also efforts made by the Village Head in overcoming these obstacles. So that the author's hypothesis "If the Implementation of Village Head Based on Leadership Techniques, then the effectiveness of the work of employees at the Tonjong Village Office, Majalengka District will Increase", the truth has been tested.Keywords: Leadership, Work EffectivenessÂ ABSTRAKÂ Penelitian ini dilakukan untuk mengetahui sejauh mana hubungan kepemimpinan Lurah dengan efektivitas kerja pegawai pada Kantor Kelurahan Tonjong Kecamatan Majalengka yang merupakan salah satu indikator yang dapat dijadikan tolak ukur keberhasilan dari pelaksanaan tugas dan fungsi Lurah. Berdasarkan pengamatan penulis selama penelitian pada Kantor Kelurahan Tonjong Kecamatan Majalengka ternyata masih ditemui beberapa indikator masalah yang menunjukkan bahwa efektivitas kerja pegawai pada kantor Kelurahan Tonjong Kecamatan Majalengka masih belum optimal. Setelah mengolah data jawaban responden ternyata : (1) Pelaksanaan kepemimpinan Lurah Tonjong, khususnya dalam penerapan teknik-teknik kepemimpinan baru mencapai 57,38% dan efektivitas kerja pegawai pada kantor Lurah Tonjong baru mencapai 56 %. (2) Terdapat hubungan antara penerapan teknik-teknik kepemimpinan dengan efektivitas kerja pegawai. Penerapan kepemimpinan yang belum optimal berpengaruh pula terhadap efektivitas kerja pegawai yang juga belum optimal. (3) Dalam penerapan teknik-teknik kepemimpinan oleh Lurah Tonjong terdapat hambatan dan terdapat pula upaya yang dilakukan oleh Lurah dalam mengatasi hambatan tersebut. Sehingga hipotesis penulis â€œJika Pelaksanaan Kepemimpinan Lurah Berdasarkan Teknik-Teknik Kepemimpinan, maka Efektivitas kerja pegawai Pada Kantor Kelurahan Tonjong Kecamatan Majalengka akan Meningkatâ€, telah teruji kebenarannya.Kata Kunci: Kepemimpinan, Efektivitas Kerja